THE EFFECT OF VITAMIN C INTAKE ON SKIN MOISTURE IN YOUNG ADULTS - Shiela Stefani (Perhimpunan Dokter Gizi Klinik Indonesia, 2026)
Background: Dry skin affects 50%–80% of Indonesia. Data from the Geriatric Department of the Dermatology and Venereology Clinic at Dr. Cipto Mangunkusumo Hospital (RSCM) in Jakarta between 2008 and 2013 indicate that dry skin is one of the ten most prevalent illnesses. Objective: Regarding skin moisture, this study tries to determine the impact of vitamin C on young adult participants. Methods: This is an observational analytical study with a quasi-experimental design carried out at Maranatha Christian University in Bandung. Medical students between 19 and 29 years old at Maranatha Christian University's Faculty of Medicine served as the study participants. Based on gender, sixty participants were split into two groups. TEWL levels were measured using the Skin Moisture Analyzer FCM-1. Vitamin C intake was obtained from a food frequency questionnaire containing food sources of vitamin C, which was then analyzed using the Nutrisurvey-2007 program, as well as vitamin C from supplementation. Results: Employing paired t-tests, the p-value for both male and female groups was <0.001, suggesting a substantial change in skin moisture levels before and after vitamin C intake. Conclusion: Young adults' skin moisture levels are affected by vitamin C intake.